Physical aspects of a nuclear explosion - Budi Santosa Budi Santosa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
This article describes the principles of nuclear power, the nature of the atomic bomb and its impact on the environment, including the climate and the resulting nuclear winter.The author also points out the effects of nuclear radiation to the living organisms, both immediate and delayed. In conclusion he emphasizes the importance of immediate cessation of nuclear tests, in the atmosphere, on the surface, submarine as well as underground, because otherwise kis bound to increase radioactivityin the environ men t which endangers future generations, even in countries which are not involved in nuclear testing.Key Words: nuclear explosion-nuclear physics- nuclear winter -radioactive fall-out-medical effects of nuclear war